2018
DOI: 10.5200/baltica.2018.31.01
|View full text |Cite
|
Sign up to set email alerts
|

Eutrophication and effects of algal bloom in the south–western part of the Curonian Lagoon alongside the Curonian Spit

Abstract: The Curonian Lagoon is the largest coastal lagoon of the Baltic Sea. The Curonian Lagoon is a hypereutrophic water body beset with two major problems: eutrophication and algal blooms. Biological and chemical data for the study of water eutrophication and algal blooms were collected from 4 sampling points in the coastal and off-shore areas at distances of 1 km and 4–5 km from the Curonian Spit during the period from April 2007 to November 2016. The ratio of mineral nitrogen/phosphorus forms created conditions f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…In natural aquatic environments, nitrate is permanently reduced to dinitrogen by denitrifying bacteria via biological denitrification [70]. With the warming weather, nitrate consumption increases due to more intense production, following the typical pattern observed in natural waters [71][72][73]. Consequently, the concentration of N/NO 3 − reaches its minimum values (Figure 3).…”
Section: Seasonal Changes In N and P Concentrations And Distribution ...mentioning
confidence: 83%
“…In natural aquatic environments, nitrate is permanently reduced to dinitrogen by denitrifying bacteria via biological denitrification [70]. With the warming weather, nitrate consumption increases due to more intense production, following the typical pattern observed in natural waters [71][72][73]. Consequently, the concentration of N/NO 3 − reaches its minimum values (Figure 3).…”
Section: Seasonal Changes In N and P Concentrations And Distribution ...mentioning
confidence: 83%
“…Additional nutrient load can also directly affect the Curonian Lagoon of the Baltic Sea, which is already subjected to significant eutrophication (Belykh et al 2013;Malfanov et al 2017;Aleksandrov et al 2018;Bartoli et al 2018;Vybernaite-Lubiene et al 2018). Phytoplankton monitoring, including toxic cyanobacteria, should be an essential part of biological monitoring in the River Neman and its major tributaries, such as the River Viliya (Neris).…”
Section: Discussionmentioning
confidence: 99%
“…The authors of [60] showed that settling velocities for the total suspended sediments in the Curonian Lagoon are very low when positively buoyant cyanobacteria are present. Pilkaitytė and Razinkovas [62] showed a strong relationship between cyanobacteria biomass and water temperature, while the authors of [70] found a moderately strong relationship between Chl-a concentrations and water temperature. These studies were a starting point for the development of a new formula for settling velocity.…”
Section: An Introduced Formula For Settling Velocitymentioning
confidence: 95%